MEMBANGUN WEBSITE PROGRAM STUDI ILMU KEPERAWATAN UNIVERSITAS SAHID SURAKART - Sukawati Novy Setiawan; Sri Huning Anwariningsih; Dahlan Susilo (Universitas Sahid Surakarta, 2017)
Nursing Science Sahid University of Surakarta is under the Faculty of Health Sciences. The information about the major is still manual and not effective. ccording to the improvement of information technology based on internet, website is the right solution to convey information fast and eficiently. The purpose of this research is to develop Nursing Science Sahid University of Surakarta website in order to simplify the information management and delivery to the students and the society. The methods which are used to collect the data are observation, interview, literature, and questionnaire method to webQual test. The data analysis used is structured based on Unified Modelling Language (UML). The making of this website uses HTML, PHP and MySQL database programming. To measure the quality of the Nursing Science Sahid University of Surakarta website, adjusted to the visitors’ or the last user’s perception, so the website test method used is webQual testing and Likert scale. From 30 questions which were asked to 30 respondents and the data are processed using SPSS 20, the testing result of the Nursing Science Sahid University of Surakarta website is 77,7%. It means that the Nursing Science Sahid University of Surakarta website is good.